Encapsulation and Characterization of Slow-Release Urea Fertilizer from the Biocomposites of Natural Zeolite-Alginate - Ida Ayu Suci; Ismail Astar; Agusalim Masulili; Setiawan (Rawa Sains: Jurnal Sains STIPER Amuntai, 2025)
Urea fertilizer has a relatively high nitrogen content (45%) compared to any other nitrogen-source fertilizers. However, due to urea's ability to dissolve readily, nitrogen fertilizer in the form of urea often has a poor efficacy. The environment will lose around 70% of the urea fertilizer during the process, including soil ammonia evaporation and urea degradation. One of the methods to increase fertilization effectiveness is to coat it with slow-release fertilizer technology. The specific objective of this study is to determine the characteristics of urea slow release fertilizer with an encapsulation technique by using natural zeolite biocomposites-alginate and nitrogen release patterns as slow release fertilizer candidates. The characteristics of biocomposites were evaluated using Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and spectrophotometer analysis for nitrogen release tests. This experiment used natural zeolite biocomposite-alginate to encapsulate the urea as an environmentally friendly slow-release fertilizer. The FTIR spectroscopy showed the presence of natural zeolite-alginate biocomposite. The SEM images showed the surface morphology of urea which had been coated by a natural zeolite-alginate biocomposite. The percentage of urea released for 72 hours at zeolite-alginate ratio of 1:1, 2:1, 3:1 were 16.10%, 21.03%, and 17.51%, respectively. This result shows that urea encapsulated by biocomposite with 1:1 ratio has the least percentage of urea release compared to the others. The biocomposite with 1:1 ratio exhibited the best performance in resisting nitrogen release from urea fertilizer. This study indicates that natural zeolite-alginate biocomposite is an alternative candidate for developing the efficiency of slow-release urea fertilizer.